2014
DOI: 10.1002/jcu.22244
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic evaluation of the thyroid size in neonates

Abstract: In full-term, euthyroid, iodine-sufficient neonates, the normal reference interval for thyroid volume measured on sonography was 0.45-1.53 ml and that for the Yasumoto ratio was 1.71-2.87. A ratio of 1.7 may be applied as the cutoff value for sonographic diagnosis of thyroid dysgenesis in full-term neonates with congenital hypothyroidism. © 2014 Wiley Periodicals, Inc. J Clin Ultrasound 43:224-229, 2015.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…It is a noninvasive nonirradiating costeffective imaging technique, but highly observer dependent. Thyroid volume in newborns varies from 0.84 -0.38 to 1.62 -0.41 mL (60-62), without significant changes during the first 3 weeks of life (63). Thyroid size can be influenced by (long-term) TSH suppression during LT4 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is a noninvasive nonirradiating costeffective imaging technique, but highly observer dependent. Thyroid volume in newborns varies from 0.84 -0.38 to 1.62 -0.41 mL (60-62), without significant changes during the first 3 weeks of life (63). Thyroid size can be influenced by (long-term) TSH suppression during LT4 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In an extremely preterm age group, delivered at less than 28 weeks of gestation, an ultrasound study showed no association between mean thyroid volume and thyroid function or between mean thyroid volume and BW 6 . Conversely, a weak correlation exists between thyroid volume and thyroid function in full‐term infants 18 . The distribution of thyroid volumes may have become relatively wide due to the inclusion of both term and preterm infants in our cohort.…”
Section: Discussionmentioning
confidence: 71%
“…The thyroid gland is part of the HPT axis, but the intensity and volume of thyroid gland on MRI have not been evaluated in detail using neonatal MRI, although the volume has been evaluated on ultrasound by a simple estimation method 6,18 . We hypothesized that the intensity and volume of the pituitary and thyroid glands in neonates may be associated with each other.…”
mentioning
confidence: 99%
“…According to the morphological findings, the DFE was classified as regular or fragmented (ie, with dysgenesis). Thyroid size was assessed with the Th/Tr ratio (Yasumoto ratio), with normal values ranging from 1.7 to 2.9 13,14 …”
Section: Methodsmentioning
confidence: 99%